Determination of basketball players` high-performance profiles in the Spanish League - Madinabeitia, I.; Pérez, B.; Gomez-Ruano, M. A., Cárdenas, D. (International Journal of Performance Analysis in Sport, 2023)
Coaches and sports scientists are looking for a way to predict performance in complex team sports such as basketball. However, concerning knowing what type of player`s profile is needed to win the competition, there is not too much information in the literature. Hence, our study had two aims: (i) to identify how the individual game-related statistics discriminate between winning and losing among different player positions through a cluster analysis; (ii) to elaborate predictive models that explain better performance through a decision tree analysis. 335 matches of the men`s Spanish League 2018/2019 were analysed, with a total of 7,345 individual statistics performances. The cluster analysis identified 3 performance groups formed by foreigners with both low (FLC; 23.8% shooting-guards) and high contributions (FHC; 32.1% centres) and Spanish with low contribution (SLC; 32.9% shooting-forwards). The decision tree analysis revealed that having players of SLC and FHC profiles predicts better results in the competition. Coaches can apply these profiles to build team composition.